2020
DOI: 10.1111/jdv.16622
|View full text |Cite
|
Sign up to set email alerts
|

Urticarial eruption in coronavirus disease 2019 infection: a case report in Tangerang, Indonesia

Abstract: Figure 2 Urticaria involving face, on the right side (a) and left side of the face (b).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 11 publications
0
27
0
1
Order By: Relevance
“…Another report from Indonesia described a 51-year-old patient who suddenly developed a generalized pruritic urticarial rash 3 days posthospitalization for COVID-19–related pneumonia. 4 A Spanish study describing urticarial lesions in a COVID-19–positive patient did not find any difference between “common urticaria” and COVID-19–related urticaria on histologic examination. 5 …”
Section: Discussionmentioning
confidence: 93%
“…Another report from Indonesia described a 51-year-old patient who suddenly developed a generalized pruritic urticarial rash 3 days posthospitalization for COVID-19–related pneumonia. 4 A Spanish study describing urticarial lesions in a COVID-19–positive patient did not find any difference between “common urticaria” and COVID-19–related urticaria on histologic examination. 5 …”
Section: Discussionmentioning
confidence: 93%
“…Near submission day, rerun of the literature for possible new case reports having dermatological manifestations was done. They also reported similar cutaneous manifestations 53,60‐72 . Initial studies on cutaneous manifestations of COVID‐19 were predominantly from China, Europe, and USA.…”
Section: Discussionmentioning
confidence: 74%
“…After eliminating the overlaps between the two search engines, we were left with 23 works investigating the relationships between SARS-CoV-2 infection and urticaria. Of these, 18 reported cases of urticaria in patients with SARS-CoV-2 infection [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]. Unfortunately, not all studies reported the characteristics of the patients studied (gender, age, timing, etc.)…”
Section: Resultsmentioning
confidence: 99%